Tradition and modernity in the structural art of steel‐glass structures in Japan. Issue 1 (28th December 2020) - Kido, Ewa Maria; Cywiński, Zbigniew; Kawaguchi, Hidetoshi
Abstract: The Committee on the Design, Construction and Production of Aesthetic Architecture, established by the Japanese Society of Steel Construction (JSSC), has for a long time stood for the promotion of appealing architecture – particularly in steel‐glass structures. Such aesthetic architecture, despite being very modern, often expresses the tradition of the particular location and its culture. The choice of structural configuration is one of the tools for achieving relevant architecture. This paper, introducing attractive and innovative steel structures combined with glass, shows several examples typical of this trend in Japan.